The winning goal - Rippin, Sally; Spartels, Stephanie (Richmond, Vic. : Hardie Grant Egmont, 2012)
Jack wants to kick a goal at soccer, but the coach had made him goalie. There's no glory in goalkeeping, is there?
For primary school age.
Keywords: Boys -- Juvenile fiction; Soccer stories; Australian; Soccer stories